2021
DOI: 10.14739/2409-2932.2021.2.233306
|View full text |Cite
|
Sign up to set email alerts
|

Study and evaluation antioxidant activity of dietary supplements with green tea extract

Abstract: The aim of the work is to determine and evaluate the antioxidant activity of dietary supplements with green tea extract, as well as to introduce conditional terms of the level of AOA. Materials and methods. The object of the study was dietary supplements of different manufactures: “Green Tea Extract” of Natural Sources, USA (DS1), “Extract of green tea” of Elit-Pharm, Ukraine (DS2) and “Green tea” of Pharmakom, Ukraine (DS3). Potentiometric measurements were conducted by pH meter Hanna 2550 (Germany) with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…According to the results of the study, it was found that the antioxidant activity of the tablets "Сaсhisept" was more than 54 % than the reference drug "Ascorutin". Accord ing to the developed conditional Maslov's classification of the level of antioxidant activity [15], we determined that "Сaсhisept" tablets have a high level of antioxidant activity, and, in turn, the reference drug "Askorutin" has a medium level (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of the study, it was found that the antioxidant activity of the tablets "Сaсhisept" was more than 54 % than the reference drug "Ascorutin". Accord ing to the developed conditional Maslov's classification of the level of antioxidant activity [15], we determined that "Сaсhisept" tablets have a high level of antioxidant activity, and, in turn, the reference drug "Askorutin" has a medium level (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to our study the total catechin content is much higher. Flavonoids is one of the biggest class of biological active substances in plant, it plays an essential role in scavenging free radicals [33]. The total flavonoid content was expressed in rutin equivalent.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we chose to apply the potentiometric method, as it is characterized by high sensitivity, rapid analysis procedure and relatively low equipment and reagents cost, and, hence, cost of analysis as a whole [33]. Based on our recent study, in determining antioxidant activity of natural antioxidants by the potentiometric method, the ethanol that was used as solvent contributed to the level of antioxidant activity of the analyzed sample.…”
Section: Discussionmentioning
confidence: 99%